Design and characterization of the liquid metal antenna optimally embedded in concrete beam prototype as an alternative strain sensor - Fernandez, Edmon O. (Animo Repository, 2016)
This paper presents the implementation of the novel dipole liquid metal antenna as an alternative strain sensor when embedded in the optimal location of a concrete beam prototype. The antenna is made up of eutectic Indium Gallium, a fluid metal alloy, encased in a microfluidic channel, namely, polydimethylsiloxane (PDMS) elastomer fabricated using McGyver-esque technique to microfabrication. The fluidic dipole antenna being highly flexible, stretchable, and reversibly deformable mimics the basic characteristics of the strain sensor where its resonant frequency is inversely related to its length. The concrete specimen was subjected to center – point loading tests where the resonant frequency of the liquid antenna embedded in it was measured simultaneously. Statistical analysis of the results show that there is a significant relationship between the displacement of the concrete specimen and the resonant frequency of the embedded antenna. © 2016 Penerbit UTM Press. All rights reserved.